PROPOSED IMPROVEMENT OF THE VENDOR EVALUATION AND SELECTION PROCESS USING RISK MANAGEMENT STRATEGY ANALYSIS AND ANALYTICAL HIERARCHY PROCESS (AHP) METHOD AT PT. PERTAMINA REFINERY UNIT VI - Komang Arie Ronny Wijaya, I
Storage tanks are an important facility in the oil and gas industrial process because storage tanks are not only a storage place for products and raw materials but also function to maintain the smooth availability of products and raw materials and can protect products or raw materials from contaminants. In operation, storage tanks require periodic inspections, cleanings, and maintenance to maintain proper oil and gas quality as well as the longevity of the facility. Storage tank maintenance is an essential service that extends the service life of storage tanks. In general, storage tank maintenance is carried out by external vendors, so the vendor evaluation and selection process are crucical to ensure project completion according to the target.